Students’ perceptions of school resource officer performance - Cooper, William N. (Criminal justice studies, 2024)
In recent years, school resource officers (SROs) and their role in the context of school safety have become a popular topic of research. In this study, we analyze data from 31,156 students from over 100 schools in Kentucky to better understand how students perceive SROs in their school environment. The findings reveal that males, students who liked having an SRO at their school, students who saw their SRO at several locations on campus during the typical school day, and students who viewed their SRO as more than a law enforcer had a higher opinion of the SRO working at their school. Interestingly, school-level variables had no impact on these relationships. Implications for policy and future research are also discussed.